Practical and Academic Aspects of Social Work Development in Lithuania - Bagdonas, Albinas (Socialinė teorija, empirija, politika ir praktika, 2001)
[full article and abstract in Lithuanian; abstract in English]Several years ago the reaction of an ordinary Lithuanian citizen, politician or even a professional (teacher, medical doctor, psychologist) to such word combinations a social work or social worker was not only awkward but often negative: What a strange word combination! Is it necessary to make references to work when naming a profession?  Maybe such notions of recent past as party work, party worker or trade union worker accounted for the negative attitude towards the said word combinations. Almost 10 years passed, and the concepts, such as social work or social worker became common. They no longer jar on nobody’s ears. However the following questions are still topical: What is social work? What do social workers do? Is it science or art? The majority of sciences have developed from philosophy. They have scientific names, usually of Latin or Greek origin. The beginning of social work is associated with charity or philanthropic activities.